Kesulitan Belajar Membaca Anak Disgrafia Pada Siswa Kelas II UPT SPF SD Negeri Mannuruki - Widia Ayu Lestari; Ummu Khaltsum; Andi Syamsul Alam (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
the main problem in this study is how the learning difficulties of children doing tutoring for Grade II students have difficulty reading in UPT SPF SD Negeri Mannuruki Kec.Tamalate Makassar City. This study aims to know the difficulty of the implementation of learning to Read Indonesian language learning students UPT SPF SD Negeri mannuruki Kec. Tamalate Makassar City. This type of research is a qualitative study to describe the implementation of the difficulty of learning to read students in Indonesian learning class II UPT SPF SD Negeri Mannuruki. The research procedure includes a sample of students in this study were second grade students with a total of 27 students. Data collection techniques were conducted by interviews, documentation and questionnaires. The collected Data were analyzed qualitatively. The results of qualitative research showed that the results of the test data analysis of reading learning difficulties obtained through the rubric of student learning difficulties in reading ability that there are 2 students (15%) who have difficulty reading while (84%) who do not have difficulty reading.in general, the factors that become learning difficulties for Class II students of UPT SPF SD Negeri Mannuruki in Reading are classified into two factors, namely factors contained within the student or externally. Based on the results of the study, it can be concluded that the factors causing the difficulty of Grade II students UPT SPF SD Negeri Mannuruki in reading difficulties are: physical factors, physicological, socio-economic factors and factors that are not appropriate education providers